Numerical test of the Schoemberg-Muir theory - Carcione, José M. (2012)
The Schoenberg-Muir theory states that an equivalent, homogeneous and anisotropic medium can be constructed from a layered medium composed of several thin layers, each anisotropic, under the assumption of stationarity. To test the theory we considered single transversely isotropic layers with different orientations of the symmetry axis and performed numerical simulations of wave propagation with a full-wave solver. The equivalent media have orthorhombic and monoclinic symmetries, respectively. The theory performed very well from the kinematical and dynamical points of view, even for strong anisotropy and layers described by media whose symmetry axes have different orientations.